Gestures and forms of contact in the literature and ritual of archaic and classical Greece (Altre Modernità, 2023)
Based on the practice of supplication, to which the moment of physical contact is central, this essay explores the functions of touch and touching in Greek literary and philosophical sources from the pre-judicial and the judicial era.
Keywords: touch; Greek literature, hiketeía